Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1515/polyeng-2019-0292
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the maximum flow length of a thin injection molded part

Abstract: One of the most significant issues, when thin parts have to be obtained by injection molding (i.e. in micro-injection molding), is the determination of the conditions of pressure, mold temperature, and injection temperature to adopt to completely fill the cavity. Obviously, modern computational methods allow the simulation of the injection molding process for any material and any cavity geometry. However, this simulation requires a complete characterization of the material for what concerns the rheological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This result is consistent with those reported in the literature about flow filling length in micro-injection molding. It was reported that, with a settled 40 MPa filling pressure (that is lower than the pressure adopted in this work), a 140 °C mold temperature is necessary to obtain about a 40 mm filling length; furthermore, filling length improves with the increase in filling pressure [21].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…This result is consistent with those reported in the literature about flow filling length in micro-injection molding. It was reported that, with a settled 40 MPa filling pressure (that is lower than the pressure adopted in this work), a 140 °C mold temperature is necessary to obtain about a 40 mm filling length; furthermore, filling length improves with the increase in filling pressure [21].…”
Section: Resultsmentioning
confidence: 88%
“…In a previous work [21], a simple equation was provided to predict the final length, L f , of a polymer flowing in a rectangular cavity of thickness H:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data such as the speed of the piston with respect to the injection time, the pressure exerted on the injection polymers, the filling time of the mold cavity and the position of the closing tools are one of the most used [51]. Various systems have been developed in order to improve the efficiency of the injection molding processes.…”
Section: State Of the Artmentioning
confidence: 99%
“…Furthermore, research papers [3][4][5][6] investigated the influence of other process parameters, specifically pressure and temperature, on final flow length. The influence of process parameters was also investigated in publications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%